2011
DOI: 10.1039/c1nr11242b
|View full text |Cite
|
Sign up to set email alerts
|

Polyaspartic acid coated manganese oxide nanoparticles for efficient liver MRI

Abstract: We report in this communication a simple, facile surface modification strategy to transfer hydrophobic manganese oxide nanoparticles (MONPs) into water by using polyaspartic acid (PASP). We systematically investigated the effect of the size of PASP-MONPs on MRI of normal liver and found that the particles with a core size of 10 nm exhibited greater enhancement than those with larger core sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 14 publications
0
41
0
1
Order By: Relevance
“…This was verified by the SAED pattern as the diffraction rings were consistent with the structure of MnO (Figure S1c, Supporting Information). Compared to the commonly used 1‐hexadecene and 1‐octadecene solvents, smaller MONs are readily yielded when the hydrocarbon chain length of the alkene solvent is reduced. It is noteworthy that highly monodispersed sub 10 nm MONs are formed by employing 1‐tetradecene as the solvent of high boiling point in our synthesis protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was verified by the SAED pattern as the diffraction rings were consistent with the structure of MnO (Figure S1c, Supporting Information). Compared to the commonly used 1‐hexadecene and 1‐octadecene solvents, smaller MONs are readily yielded when the hydrocarbon chain length of the alkene solvent is reduced. It is noteworthy that highly monodispersed sub 10 nm MONs are formed by employing 1‐tetradecene as the solvent of high boiling point in our synthesis protocol.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the r 1 relaxivity is expected to increase as the particle size of MONs decreases. For example, Chen and co‐workers found that MONs with a size of 10 nm exhibited a greater positive contrast ability than those with larger sizes . Hollow‐structured MONs are also attractive candidates as T 1 contrast agents because they exhibit high surface‐to‐volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Phantom studies indicated contrast enhancement depending on the concentration of both particles and amount of Gd loaded into the construct . Manganese‐based contrast agents surface coated with polymeric nanomaterials are gaining importance to be explored as alternate T1 agents …”
Section: Polymeric Mr Contrast Agentsmentioning
confidence: 99%
“…However, recent synthesis of manganese oxide‐based NPs could lead to a resurgence of manganese as an MRI contrast agent, and a recent report by Zhang et al demonstrate the efficacy of Mn 2+ ions as imaging probes for visualizing delivery of cancer therapeutic drugs . Also, manganese oxide NPs (MONPs) are T2/T2 * active CAs, but they also degrade in water within a reasonable time frame (hours to days) . This is interesting for MRI applications because MONPs that degrade, release Mn 2+ ions, which are very efficient T1 CAs .…”
mentioning
confidence: 99%